2021
DOI: 10.1002/nau.24787
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between illness perception and worsening of interstitial cystitis/painful bladder syndrome symptoms: A cross‐sectional study

Abstract: Objective: To evaluate disease perception in a cohort of patients with interstitial cystitis/painful bladder syndrome (IC/PBS) using the Brief Illness Perception-Questionnaire (BIP-Q) and to evaluate how this might relate to disease severity.How to cite this article: Garba K, Avery M, Yusuh M, et al. The relationship between illness perception and worsening of interstitial cystitis/ painful bladder syndrome symptoms: A cross sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Apart from the physical effects (Lee et al, 2014), IC/BPS negatively affects the quality of life and emotional well‐being of the patients (Garba et al, 2021). Previous studies have reported that IC/BPS is closely associated with family, social functioning and mental health, particularly related to negative psychological states such as depression, anxiety and panic (McKernan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the physical effects (Lee et al, 2014), IC/BPS negatively affects the quality of life and emotional well‐being of the patients (Garba et al, 2021). Previous studies have reported that IC/BPS is closely associated with family, social functioning and mental health, particularly related to negative psychological states such as depression, anxiety and panic (McKernan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%